2020
DOI: 10.1097/mjt.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Lactam Plus Macrolide Versus Fluoroquinolone on 30-Day Readmissions for Community-Acquired Pneumonia

Abstract: Background: Antibiotic therapy with a macrolide and β-lactam or a fluoroquinolone for the empirical treatment of community-acquired pneumonia (CAP) in an inpatient non–intensive care setting is recommended per guidelines. Studies show that these treatments have similar outcomes, including death, adverse effects, and bacterial eradication. However, a comparison of 30-day readmission rates between these treatments is limited. Study Question: To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…With its wide application in bacterial pneumonia, the detection rate and infection rate of various drug-resistant bacteria have also increased dramatically ( Hu et al, 2018 ), resulting in a significant increase in the incidence of drug-resistant bacterial pneumonia. Overuse of antibiotics, particularly fluoroquinolones ( Møller Gundersen et al, 2019 ; Gilbert et al, 2020 ), may increase the risk of MDR bacteria selection and nosocomial pneumonia, though convincing clinical data to support these possibilities are lacking ( Tamma et al, 2012 ). The clinical research of Adrie et al (2013) showed that the rates of secondary identification rate of MDR bacteria in the monotherapy and dual therapy groups was similar to the incidence of nosocomial pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…With its wide application in bacterial pneumonia, the detection rate and infection rate of various drug-resistant bacteria have also increased dramatically ( Hu et al, 2018 ), resulting in a significant increase in the incidence of drug-resistant bacterial pneumonia. Overuse of antibiotics, particularly fluoroquinolones ( Møller Gundersen et al, 2019 ; Gilbert et al, 2020 ), may increase the risk of MDR bacteria selection and nosocomial pneumonia, though convincing clinical data to support these possibilities are lacking ( Tamma et al, 2012 ). The clinical research of Adrie et al (2013) showed that the rates of secondary identification rate of MDR bacteria in the monotherapy and dual therapy groups was similar to the incidence of nosocomial pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals at higher risk for these complications include those with hypertension, a history of circulatory blockages or aneurisms, select genetic disorders, and the elderly [21,[26][27][28]. Efficacy is similar between the two regimens; however, some studies have demonstrated that fluoroquinolone monotherapy leads to a reduces hospital LOS [9,[28][29][30][31]. β-Lactam plus macrolide combination therapy was the **Counts of less than or equal to 20 are displayed as ≤20 to comply with the All of Us data and statistic dissemination policy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Both options are included as first-line choices in recent ATS guidelines [1]. Several studies have reported an association between the use of the combination of β-lactams plus macrolide and lower mortality in CAP, when compared to the use of β-lactams in monotherapy [28,29]. However, Postma et al [30].…”
Section: Discussionmentioning
confidence: 99%